IMPACT OF DISCIPLINE ISSUES ON SCHOOL EFFECTIVENESS: THE VIEWS OF SOME GHANAIAN PRINCIPALS - Inusah Salifu; Joseph S Agbenyega (MIER Journal of Educational Studies Trends and Practices, 2012)
This research focuses on discipline issues as one of the major concerns of educators in public schools in Ghana. Qualitative and quantitative enquiries were undertaken into discipline issues and their implications on student learning as perceived by senior high school principals in Brong Ahafo Region of Ghana. The study reveals that senior high school administrators perceived indiscipline as an issue affecting their administration, and prevented the provision of congenial atmosphere for effective teaching and learning. In addition, it tarnished the image of the schools before the outside world, thus discouraging donors, parents and other interest groups from having interest in the schools. Recommendations for involvement of students in decision making and the provision of guidance and counselling services are explored.